2022
DOI: 10.3390/nu14081613
|View full text |Cite
|
Sign up to set email alerts
|

Association of Abnormal Iron Status with the Occurrence and Prognosis of Peritoneal Dialysis-Related Peritonitis: A Longitudinal Data-Based 10-Year Retrospective Study

Abstract: This retrospective study investigated the effect of iron status on peritonitis by analyzing longitudinal iron parameters in peritoneal dialysis (PD) patients. Patients who received PD at our center from 1 January 2006 to 31 December 2015 were included and followed up until 31 December 2017. According to the joint quartiles of baseline transferrin saturation and ferritin, iron status was categorized as reference iron status (RIS), absolute iron deficiency (AID), functional iron deficiency (FID), and high iron s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 41 publications
2
4
0
Order By: Relevance
“…At least in part, this may be due to the fact that current analysis excluded patients with conditions that may have at least potentially contributed to absolute or functional iron deficiency. Fourteen percent of patients in our cohort had high iron status, comparable to other reports (6,8). These patients tended to have the lowest Hb level despite the highest median CERA dose, and worse preserved RRF.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…At least in part, this may be due to the fact that current analysis excluded patients with conditions that may have at least potentially contributed to absolute or functional iron deficiency. Fourteen percent of patients in our cohort had high iron status, comparable to other reports (6,8). These patients tended to have the lowest Hb level despite the highest median CERA dose, and worse preserved RRF.…”
Section: Discussionsupporting
confidence: 86%
“…Only 9% patients met the criteria for absolute iron deficiency, while none had functional iron deficiency. Our results stand out significantly from the literature data according to which iron deficiency prevalence exceeds 26% (6,8,16). At least in part, this may be due to the fact that current analysis excluded patients with conditions that may have at least potentially contributed to absolute or functional iron deficiency.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…A large US cohort study (N=22,820) showed an increased risk of infection-related events and infection-related mortality with high IV doses of Fe in HD ( 26 ), and a meta-analysis by Litton suggested IV Fe was associated with a significantly higher incidence of infection compared with either oral Fe or no Fe supplementation ( 27 ). A retrospective study analyzed the longitudinal Fe parameters of peritoneal dialysis (PD) patients and proposed Fe excess was associated with the onset of peritonitis and poor prognosis ( 28 ). There are also recent conflicting reports of randomized controlled trials concerning the association between IV Fe administration and infections.…”
Section: Discussionmentioning
confidence: 99%
“…Before starting the prescription of ESAs according to KDIQO recommendations, it is necessary to rule out acute inflammation, regulate secondary hyperparathyroidism (SHPT) and replace iron depots [23,24], which was carried out in our cohort. The assessment of feremia in PD patients is performed on the basis of serum Fe, TIBC and ferritin [25]. Substitution was carried out by administering heme and nonheme Fe orally, considering that PD is a form of home treatment [24,25].…”
Section: Discussionmentioning
confidence: 99%